Rice transcription factors OsNIGT2/3 regulate nitrogen acquisition by repressing OsNRTs and OsAMTs under high-nitrogen conditions - Du, Hongyang; Cong, Xihan; Ruan, Xinmin; Yang, Yang; Shi, Fuzhi; Luo, Yanchang; Luo, Zhixiang (Frontiers in Plant Science, 2025)
IntroductionNitrogen is a crucial nutrient for crop growth, yet its utilization efficiency is generally low, leading to resource waste and serious environmental problems. Future agricultural sustainability requires improved crop NUE. In this study, we investigated the functions of the rice transcription factors OsNIGT2 and OsNIGT3 in nitrate uptake under high-nitrogen conditions.MethodsHydroponic experiments and field tests were conducted to investigate the effects of OsNIGT2 and OsNIGT3 on physiological phenotypes and nitrogen use efficiency. Transcriptome analysis was used to explore the genome-wide transcriptional landscape of the two genes in response to nitrate availability. DNA affinity purification sequencing (DAP-seq) was employed to identify genomic sites bound by OsNIGT2, subsequently, yeast one-hybrid and transient expression assays verified the regulatory effects of OsNIGT2 and OsNIGT3 on key genes.ResultsThe double mutants of OsNIGT2 and OsNIGT3 presented significantly greater dry weights, nitrogen contents, total amino acid contents, and nitrate levels than the WT, whereas the single mutants presented no significant differences. These findings indicate the functional redundancy of OsNIGT2 and OsNIGT3 in regulating nitrogen uptake and assimilation. OsNIGT2 and OsNIGT3 act as transcriptional repressors, negatively regulating the expression of nitrogen absorption-related genes. Furthermore, DAP-seq identified potential targets bound by OsNIGT2, highlighting its role in the expression of several nitrogen and phosphorus utilization-related genes. Additionally, field tests shown that OsNIGT2 and OsNIGT3 knockout promotes both grain yield and NUE. This study provides potential genetic targets for improving yield and NUE in rice and other crops, laying a significant foundation for future crop improvement.